Inventory Information System in Benostore Stores - Arrotama Hafed Mawan; Dimas Aryo Anggoro (Emitor: Jurnal Teknik Elektro, 2021)
Benostore shop is a shop that sells clothing equipment in Surakarta. Inventory management at Benostore stores is still conventional with the records in the ledger so that its performance is limited. Then an inventory information system was created to optimize inventory management at the Benostore store. The method used is the SDLC method with a waterfall approach using UML (integrated modeling language) which consists of use case diagrams and activity diagrams. This system is designed using the Hypertext Preprocessor (PHP) web programming language with the CodeIgniter version 3 framework and MySQL which is used for database design and data storage. This system will be tested using the BlackBox method and user acceptance test (UAT). UAT testing uses the interview method involving shop owners and employees. This research produces an inventory system that can be implemented in the Benostore shop.